2020
DOI: 10.48550/arxiv.2002.01514
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Generalized Ricci flow on nilpotent Lie groups

Abstract: We define solitons for the generalized Ricci flow on an exact Courant algebroid, building on the definitions of [Gar19]. We then define a family of flows for left-invariant Dorfman brackets on an exact Courant algebroid over a simply connected nilpotent Lie group, generalizing the bracket flows for nilpotent Lie brackets in a way that might make this new family of flows useful for the study of generalized geometric flows, such as the generalized Ricci flow. We provide explicit examples of both constructions on… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 5 publications
0
3
0
Order By: Relevance
“…A Perelman-type F-functional for this was found in [19], and an expander entropy functional was found in [26]. Some recent results in the homogeneous setting have appeared [20], as well as a stability result near Ricci-flat metrics [23]. In [9] it was shown that the equation reduces to Ricci-Yang-Mills flow in the case of a U (1) principal bundle over a Riemann surface.…”
Section: Symmetry Reductionsmentioning
confidence: 96%
“…A Perelman-type F-functional for this was found in [19], and an expander entropy functional was found in [26]. Some recent results in the homogeneous setting have appeared [20], as well as a stability result near Ricci-flat metrics [23]. In [9] it was shown that the equation reduces to Ricci-Yang-Mills flow in the case of a U (1) principal bundle over a Riemann surface.…”
Section: Symmetry Reductionsmentioning
confidence: 96%
“…It would be interesting to carry out a similar analysis for left-invariant solutions of generalized Ricci flow in other classes of Lie groups, which help us to understand qualitative properties of the equations. The case of nilpotent Lie groups has been studied in [139] (see also [21,59] in the setting of pluriclosed flow in Chapter 9).…”
Section: Without Loss Of Generality We Can Asssumementioning
confidence: 99%
“…Recently, the gRF has been related to some geometric flows in Hermitian Geometry, like e.g. the pluriclosed flow and the generalized Kähler Ricci-flow [5,17,21], and it has been studied on nilpotent Lie groups [12]. We refer the reader to [5] for an extensive introduction to this topic.…”
Section: Introductionmentioning
confidence: 99%